Discussion of Materiality Allocation in Audit Planning: A Feasibility Study - Scott, William R. (Journal of Accounting Research, 1979)
William R. Scott, Discussion of Materiality Allocation in Audit Planning: A Feasibility Study, Journal of Accounting Research, Vol. 17, Studies on Auditing-Selections from the "Research Opportunities in Auditing" Program (1979), pp. 231-238